Sustainability assessment of food industry with the approach of water, energy and food nexus - TSENG,Cheng-jui (2022)
Abstract The development of the food industry, along with the protection of water and energy resources, is crucial for sustainable economic growth and human well-being. Water, energy and food nexus approaches can help reduce food waste and other resources by adopting policies and regulations based on comprehensive information and Nexus that promote the use of more efficient production technologies in terms of water and energy consumption against food waste. This paper aims to identify the potential of integrated management of food industry, water and energy in Sulaimaniyah. In this paper, the WEAP planning system, as well as Excel software, have been used. Also, five scenarios were proposed that predicted the level of food demand and shortage of water and energy resources from 2021 to 2025. Considering the simultaneous development of food industry and agriculture, scenario 5 was selected as the best scenario. In this scenario, simultaneous management of water and energy demand is also considered to increase food production. In scenario 5, the amount of water supply is 94.85%, which indicates that it is more effective than in scenarios 3 and 4. Also, in scenario 5, with the increase in surface water use and full use of electric pumps instead of diesel, the amount of energy required to pump water from the aquifer is 55% and 49% less than in scenarios 3 and 4 respectively.